Scientific Creativity and Synergetic Thinking - Aripova Zulfiyaxon Salijanovna (Scientific Trends, 2025)
This article describes the continuous movement associated with scientific creativity. And at the same time, it was suggested that through synergetic thinking we can gain knowledge about the principle of self-organization in nature, which creates complex systems from simple ones when conducting scientific research.
Keywords: Synergetic thinking, scientific creativity, potential, entropy and pantropy, bifurcation, fluctuation, disorder, dissociation, attractor, open system, heuristic ideas.